Wooden Species in the Urban Green Areas and their Role in Improving the Quality of the Environment - Stratu Anişoara; Costică Naela; Costică Mihai (Present Environment and Sustainable Development, 2016)
The purpose of this paper is to underline the role of some wooden species in different units of green areas in Iasi municipality in improving the quality of the environment. By regular visits in the field, we have identified the wooden species frequent in different areas; based on the bibliography in the field, we underlined the ecological characteristics, the resistance to unfavourable climate factors, and the role of these species in improving the quality of the environment. Most species taken into account are resistant to extremely cold weather and to drought; are considered resistant (Acer negundo, Acer pseudoplatanus, Hibiscus syriacus, Ligustrum vulgare) or present moderate resistance (Aesculus hippocastanum, Acer platanoides, Philadelphus coronarius) to polluting elements in the atmosphere. The wooden species considered in this study have profound influence on the environment: they regulate the urban microclimate; they contribute to the concentration reduction of some atmospheric pollutants, the noise level; they improve the edaphical conditions and contribute to the soil consolidation. Some species can be used as bio-monitors of the pollution in urban areas.